Effects of Synergism of Mindfulness Practice Associated With Transcranial Direct-Current Stimulation in Chronic Migraine: Pilot, Randomized, Controlled, Double-Blind Clinical Trial - Pimenta, Luana Dias Santiago; de Araújo, Elidianne Layanne Medeiros; Silva, Joyce Poláine dos Santos; França, Jamyson Júnior; Brito, Pedro Nascimento Araújo; de Holanda, Ledycnarf Januário; Lindquist, Ana Raquel; Lopez, Luiz Carlos Serramo; Andrade, Suellen Marinho (Frontiers in Human Neuroscience, 2021)
Chronic migraine is a difficult disease to diagnose, and its pathophysiology remains undefined. Its symptoms affect the quality of life and daily living tasks of the affected person, leading to momentary disability. This is a pilot, randomized, controlled, double-blind clinical trial study with female patients between 18-65 years old with chronic migraine. The patients underwent twelve mindfulness sessions paired with anodal transcranial direct-current stimulation (tDCS) over the left dorsolateral prefrontal cortex (DLPFC), with current intensity of 2mA applied for 20 minutes, three times a week for four weeks. In addition, 20 minutes of mindfulness home practices were performed by guided meditation audio files. A total of 30 participants were evaluated after the treatment, and these were subdivided into two groups - active tDCS and sham tDCS, both set to mindfulness practice. The FFMQ-BR (Five Facet of Mindfulness Questionnaire), MIDAS (Migraine Disability Assessment) and HIT-6 (Headache Impact Test) questionnaires were used to evaluate the outcomes. After the treatment, the active mindfulness and tDCS group showed better results in all outcomes. The sham group also showed improvements, but with smaller effect sizes compared to the active group. The only significant difference in the intergroup analysis was the outcome evaluated by HIT-6 in the post treatment result. Our results provide the first therapeutic evidence of mindfulness practices associated with left DLPFC anodal tDCS with a consequent increase in the level of full attention and analgesic benefits in the clinical symptoms of patients with chronic migraine.